1977
DOI: 10.1128/jb.129.3.1628-1631.1977
|View full text |Cite
|
Sign up to set email alerts
|

Protoplast formation of selected Mycobacterium smegmatis mutants by lysozyme in combination with methionine

Abstract: Lysozyme-sensitive mutants of Mycobacterium smegmatis, isolated by nitrosoguanidine treatment, have been converted into protoplasts in a nutritionally enriched medium containing lysozyme and DL-methionine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The conversion of cells to protoplasts in S medium plus MgCl2 occurred over a period of several days. This slow process is similar to the case in Mycoplasma smegmatis where treatment with lysozyme and methionine led to protoplast formation over a period of 2 weeks (25).…”
Section: 0fsupporting
confidence: 72%
“…The conversion of cells to protoplasts in S medium plus MgCl2 occurred over a period of several days. This slow process is similar to the case in Mycoplasma smegmatis where treatment with lysozyme and methionine led to protoplast formation over a period of 2 weeks (25).…”
Section: 0fsupporting
confidence: 72%
“…The investigators hypothesized that the spherical state is irreversible because DivIVA requires negative membrane curvature to localize and to form a new pole (Meniche et al, 2014;Lenarcic et al, 2009;Huang & Ramamurthi 2010). However, we noted that spherical mycobacterial cells generated by cell wall digestion (Rastogi & Venkitasubramanian 1979;Yabu and Takahashi 1977;Udou et al, 1982;Udou et al, 1983), rather than DivIVA depletion, have been reported to reform rods. Spheroplasting offered a means to track de novo morphogenesis from spherical cells that were formed independently of DivIVA status.…”
Section: Resultsmentioning
confidence: 68%
“…For measurement of the incorporation of labelled precursors into macromolecules, the method of Yabu & Takahashi (1977) was employed. Spheroplasts were suspended in stabilizing buffer at a concentration of 1 mg/ml protein.…”
Section: Macromolecular Synthesis In Spheroplastsmentioning
confidence: 99%